POLITIK IDENTITAS ANIMAL POP DANCE: Subbudaya dan Gaya Hidup Hibrid - Imam Setyobudi (Jurnal Sosiologi Reflektif, 2017)
Post-colonial theories bear two perspectives. First, Said argues that the ideological and concrete framework of ideology and colonial knowledge stands firmly, neatly, and perfectly without any crack that remains entrenched. Bhabha argues that the building of ideology and colonial knowledge full of cracks necessitates the creative opportunity of creating hybrid traditions and cultures that are not merely extensions of the colonial army, but also not the real bumiputera: ambiguity and ambivalence.This article, tracking the identity politics that construct a subculture with a particular lifestyle through the creation of Animal Pop Dance choreography. An Indonesian hip hop which is a hybridization process of hip hop grown in the United States by Africa-America is mixed with three local Indonesian dance (Javanese, Sundanese, Papuan) traditions of animal behavior. The results show Animal Pop Dance is a hybrid tradition and culture that aspires to escape from the grip of dichotomous thinking patterns in post-colonial contexts.Teori paska-kolonial melahirkan dua perspektif. Pertama, Said berpendapat kerangka-beton ideologi dan pengetahuan kolonial berdiri kokoh, rapi, dan sempurna tanpa retakan yang masih bercokol utuh. Bhabha berpendapat bangunan ideologi dan pengetahuan kolonial penuh retakan meniscayakan peluang kreatif menciptakan tradisi dan budaya hibrid yang bukan sekadar kepanjangan tangan kolonial semata, akan tetapi juga bukanlah bumiputera yang sesungguhnya: ambiguitas dan ambivalen. Artikel ini, pelacakan terhadap politik identitas yang mengkonstruksi sebuah subbudaya dengan gaya hidup tertentu melalui penciptaan koreografi Animal Pop Dance. Suatu hip hop Indonesia yang merupakan proses hibridisasi hibrid dari hip hop yang tumbuh di Amerika Serikat oleh kalangan Africa-America dicampuradukan dengan tiga tari tradisi lokal Indonesia (Jawa, Sunda, Papua) bertema perilaku binatang. Hasil penelitian memperlihatkan Animal Pop Dance adalah tradisi dan budaya hibrid yang berhasrat melepaskan diri dari cengkeraman pola berpikir dikotomi dalam konteks paska-kolonial.   Keywords: politic of identity, animal pop dance, subculture, lifestyle, hybrid